2019
DOI: 10.1017/s1047951119001112
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of low-intensity biopsy surveillance for rejection in paediatric cardiac transplantation

Abstract: Background:Significant inter-centre variability in the intensity of endomyocardial biopsy surveillance for rejection following paediatric cardiac transplantation has been reported. Our aim was to determine if low-intensity biopsy surveillance with two scheduled biopsies in the first year would produce outcomes similar to published registry outcomes.Methods:A retrospective study of paediatric recipients transplanted between 2008 and 2014 using a low-intensity biopsy protocol consisting of two surveillance biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Evers et al reported outcomes from their center demonstrating that a low‐intensity RSB schedule (two in the first year and annually thereafter) produced intermediate‐term outcomes similar to published registry outcomes up to 5‐year post‐HT 39 …”
Section: Outcomes Of High‐ Versus Low‐frequency Routine Surveillance ...mentioning
confidence: 68%
See 1 more Smart Citation
“…Evers et al reported outcomes from their center demonstrating that a low‐intensity RSB schedule (two in the first year and annually thereafter) produced intermediate‐term outcomes similar to published registry outcomes up to 5‐year post‐HT 39 …”
Section: Outcomes Of High‐ Versus Low‐frequency Routine Surveillance ...mentioning
confidence: 68%
“…Evers et al reported outcomes from their center demonstrating that a low-intensity RSB schedule (two in the first year and annually thereafter) produced intermediate-term outcomes similar to published registry outcomes up to 5-year post-HT. 39 Keypoint: The available evidence suggests that a reduction in RSB intensity from high-frequency to low-frequency can be done safely with no impact on early and mid-term survival. Unfortunately, there is a paucity of pediatric data evaluating long-term outcomes (beyond the first 5 years) stratified by RSB intensity.…”
Section: Outcome S Of Hi G H -Ver Sus Low-frequen C Y Routine Surveil...mentioning
confidence: 99%
“…Using a larger population and whole-heart imaging, we have demonstrated a difference in T1 values between cases of rejection and cases without rejection, when rejection is defined clinically by necessity of treatment rather than exclusively by biopsy grade. Further, due to significant inter-center variability in the frequency of EMB for rejection surveillance, prior studies have investigated the yield of EMB and its impact on outcomes in the pediatric population [ 46 , 47 ]. Studies investigating frequency of EMB both in the first year post-transplantation [ 47 ] when rejection risk is highest as well as long-term routine surveillance [ 46 ], demonstrated similar outcomes between high intensity and low intensity protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Further, due to significant inter-center variability in the frequency of EMB for rejection surveillance, prior studies have investigated the yield of EMB and its impact on outcomes in the pediatric population [ 46 , 47 ]. Studies investigating frequency of EMB both in the first year post-transplantation [ 47 ] when rejection risk is highest as well as long-term routine surveillance [ 46 ], demonstrated similar outcomes between high intensity and low intensity protocols. Adult studies have supported discontinuing routine EMB for long-term surveillance [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since these cases are elective and likely scheduled surveillance, the question for the practitioner is can non‐invasive markers for rejection largely replace the need for a scheduled surveillance biopsy? Is there precedence in centers performing less surveillance biopsies without inferior outcomes? 2,3 And if the patient has no findings to suggest rejection, not admitted, or the biopsy is not deemed “urgent”, would the practitioner treat for rejection if the histology meets certain pre‐specified pathological criteria? Albeit low, based on the reaffirmed serious complication frequency reported in the study, the practitioner should be prepared to answer these questions before subjecting a patient to biopsy.…”
mentioning
confidence: 99%